Simple mathematical model proposition of herbicide persistence in the soil - Fuentes, Ricardo; Umanã, Luis; Manquián, Nimia; Cristi, Rául (Pesquisa Agropecuaria Brasileira, 2000)
The present study proposes a simple model of persistence of herbicides in soil based on a series of modifications to the model developed by Walker & Barnes. The model proposed simulates the daily degradation of a herbicide in soil, through three submodels: a) soil temperature submodel, b) soil moisture content submodel and, c) degradation of the product submodel. A theoretical description of the modifications introduced to the model and a detail of the software program in language BASIC are given. An independent validation of each one of the modified submodels was done and it concludes that all of them improve the efficiency of prediction of the original model. The validation of the degradation submodel was made using field obtained information in two different soils from the herbicides metsulfuron-metil and triasulfuron. Finally it is possible to conclude that the proposed model would be efficient in the simulation of the persistence of these sulfonylureas in the soil, using a kinetic first degree model for metsulfuron-mehtyl and one of second degree for triasulfuron.